2018
DOI: 10.3390/su10041211
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Changing Forest Management Areas on Forest Landscapes and Habitat Patterns in Northeastern China

Abstract: The management of multi-use forests often drives forest fragmentation, which leads to decreased habitat areas and quality. We explored suitable habitat distributions of cervids to evaluate the conflict between small-scale human management and large-scale habitat conservation in human-disturbed forest landscapes. We estimated the potential habitat of roe deer (Capreolus pygargus) and determined the contribution of multiple environmental factors to habitat distribution using the presence of roe deer (N = 106) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The Great Khingan Range is a well-known mountain range in northeast China, bordering the Russian Far East in the north (49 • 22'57" N, 123 • 09'24" E) [36,37]. The area has a large expanse of hills with an elevation of 1200-1300 m a.s.l., and it belongs to the cold temperate zone continental monsoon climate.…”
Section: Introductionmentioning
confidence: 99%
“…The Great Khingan Range is a well-known mountain range in northeast China, bordering the Russian Far East in the north (49 • 22'57" N, 123 • 09'24" E) [36,37]. The area has a large expanse of hills with an elevation of 1200-1300 m a.s.l., and it belongs to the cold temperate zone continental monsoon climate.…”
Section: Introductionmentioning
confidence: 99%
“…Distance to a forest management area was found to affect habitat suitability with a contribution probability ranging from 4% to 6% and, with an increase in the management area, suitable habitat for roe deer decreased. Habitat suitability for roe deer reached its peak about 1300 m from a forest management area (Wu et al, 2018). Bonnot et al (2013) found that the average distance of a GPS location to the nearest human dwelling was 224 m (range: 1.8-995.8 m) and the average distance to the nearest road was 247 m (range: 0.2-818.1 m).…”
Section: The Environmental Factors Of Habitat Suitability Changesmentioning
confidence: 99%
“…MaxEnt is a general-purpose machine learning method for making predictions or inferences from incomplete information [8]. The intent of MaxEnt is to estimate a target probability distribution by finding the probability distribution of maximum entropy (which is most spread out, or nearly uniform), subject to a set of constraints that represent incomplete information about the target distribution [7,9]. MaxEnt has good performance in modeling species geographic distribution with presence-only data [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The intent of MaxEnt is to estimate a target probability distribution by finding the probability distribution of maximum entropy (which is most spread out, or nearly uniform), subject to a set of constraints that represent incomplete information about the target distribution [7,9]. MaxEnt has good performance in modeling species geographic distribution with presence-only data [9][10][11][12]. However, different climatic factors were selected to simulate the relationship between species and climate, and the distribution of species was then predicted in previous studies.…”
Section: Introductionmentioning
confidence: 99%